Tinjauan Hukum tentang Tindak Pidana terhadap Agama dan Kepercayaan Menurut KUHP 2023 dengan Pendekatan Keadilan Korektif - Abdullah, Fathin; Safira, Rifka; Faradiz, Naqia Annisa (Indonesian Journal Publisher, 2025)
This study aims to analyze the legal regulation of criminal offenses against religion and belief under Indonesia’s 2023 Penal Code (KUHP) and to assess the effectiveness of the corrective justice approach in preventing legal misuse. The old Article 156a of the previous KUHP was often criticized for its vague interpretation and misuse against religious minority groups. The 2023 Penal Code introduces significant reforms, including more detailed provisions under Chapter VII and alternative sanctions such as community service. Using a normative legal method with statutory, conceptual, and case study approaches, the research finds that the 2023 Penal Code provides a more systematic and proportional framework for religion-related offenses. Furthermore, the adoption of corrective justice enables more restorative outcomes through mediation, restitution, and the avoidance of excessive criminalization. However, several challenges remain in its implementation, including overlaps with Law No. 1/PNPS/1965, limited understanding among law enforcement of corrective justice, and the absence of clear technical guidelines. The study concludes that the 2023 Penal Code marks a progressive step toward a more humane and modern criminal justice system. Its success, however, depends on a paradigm shift among law enforcement officials and regulatory harmonization. Future research should adopt an empirical approach to evaluate the practical application of corrective justice in religious diversity contexts.